PENGARUH OLAHRAGA TRADISIONAL SUNDA MANDA (ENGKLEK) TERHADAP MOTORIK KASAR GERAK LOKOMOTOR MELOMPAT PADA ANAK DIFABEL (TUNAGRAHITA RINGAN) SLB SISWA BUDHI SURABAYA - FANDY ACHMAD SHOLIKAN, KURNIA; SUDIJANDOKO, ANDUN (Jurnal Kesehatan Olahraga, 2019)
Mild mentally retarded children have limitations in adaptive abilities and especially gross motor skills which are very important for everyday life. In Surabaya Budhi Student SLB the majority of students are children with mild Granny, researchers see mentally retarded children still not good at gross motor skills. The purpose of this study was to determine the effect of traditional Sunda manda (engklek) games on gross motoric abilities of locomotor jumps in mild mentally retarded children at Budhi Surabaya Student SLB. This study was a quantitative study with the research design used was the design of one group pretest-posttest design. The sample in this study were 10 mild mentally retarded children according to the criteria set by the researcher, using purposive sampling technique. Statistical test using t-test using paired samples test with a significance value of p <0.05. The results of thestudies pretetsshow and posttest that the calculated t-value is -3,092 with probability (Sig) 0,013 indicating the value of p-value paired samples <0.05. Based on the data, it can be concluded that there is influence on traditional Sunda manda (engklek) game on gross motoric ability of locomotor jumps in mild mentally retarded children in Budhi Surabaya Student SLB. Keywords : Traditional Sunda manda game (engklek), gross motoric, mild mental retardation